Flow control techniques for Onyx embolization of intracranial dural arteriovenous fistulae - Shi, Zhong-Song; Loh, Yince; Gonzalez, Nestor; Tateshima, Satoshi; Feng, Lei; Jahan, Reza; Duckwiler, Gary; Viñuela, Fernando (Journal of neurointerventional surgery, 2013)
Objectives Experience of flow control techniques during endovascular treatment of intracranial dural arteriovenous fistulas (DAVFs) using the Onyx liquid embolic system is reported, with an emphasis on high flow shunts. Methods Data were evaluated in patients with DAVFs treated endovascularly with Onyx. Adjunctive techniques with coils, acrylics and balloon assistance were utilized to reduce the rate of flow with transarterial and transvenous approaches. Results The following types of adjunctive techniques were used in 58 patients who underwent a total of 84 embolization sessions with Onyx: transvenous coiling with transvenous or transarterial Onyx embolization in 36 patients, transarterial coiling with transarterial Onyx embolization in eight patients, arterial or venous balloon assisted technique with transarterial or transvenous Onyx embolization in 11 patients, transarterial high concentration acrylics with transarterial Onyx embolization in one patient and staged transarterial or transvenous coiling and Onyx embolization in two patients. Complete obliteration of the fistulae was achieved in 41 patients (70.7%) and 27 patients (65.9%) with high flow fistulae after endovascular treatment alone. Periprocedural complications were encountered in 16 patients, and 13 complications were associated with the adjunctive techniques. There were four neurologic and two non-neurologic clinical sequelae. Distal Onyx migration occurred in four, microcatheter retention in three and cranial neuropathy in three patients. There was one instance each of cerebellar hemorrhage, thromboembolism, coil stretching and retention, and dissection. 56 survivors experienced complete resolution or significant improvement of their symptoms on follow-up. Conclusions Flow control techniques are safe and effective adjunctive methods in primary endovascular Onyx embolization of high flow DAVFs.